Fleksibilitas Hukum Islam dalam Menjawab Tantangan Hukum Keluarga, HAM dan Ekonomi Modern: Tinjauan Maqashid Syariah - Kaunang, Gebby Chyntia Detta; Husain, Safarni (Tasyri' : Journal of Islamic Law, 2025)
Islamic law is known as a divine legal system that has high flexibility in responding to the dynamics of society. In the modern era, challenges in the fields of family law, human rights, and the economy—especially the Islamic finance sector—demand contextual adjustments to keep Islamic law relevant. This article aims to examine how the flexibility of Islamic law is applied in dealing with these challenges through the maqashid sharia approach. This research uses a descriptive qualitative method with a normative-theological approach, through a literature study of classical and contemporary literature. The results of the study show that the principles of sharia maqashid, which include the protection of religion, soul, intellect, descent, and property, are an important foundation in answering modern problems. In the context of family law, the flexibility of Islamic law is reflected in regulatory updates such as the Compilation of Islamic Law (KHI) that is responsive to the needs of women and children. On human rights issues, the principles of justice and respect for human dignity have been embedded in Islamic teachings, although they still face challenges of interpretation. Meanwhile, the economic sector has shown significant success through the growth of an inclusive and adaptive Islamic banking industry. With the approach of sharia maqashid and contextual ijtihad, Islamic law has proven to be able to transform into a legal system that is not only normative, but also solutive and humanist in modern life.